SANKSI PIDANA PELAKU PENCABULAN TERHADAP ANAK YANG DILAKUKAN ANGGOTA KELUARGA (PUTUSAN NOMOR 1162/PID.B/2021/PN.BDG): Criminal Sanction for Child Abuse Performed by Family Members (Decision Number 1162/Pid.B/2021/PN.Bdg) - Syilvia Widyastuti; Vientje Ratna Multiwijaya (Universitas Trisakti, 2024)
The crime of child molestation is the act of someone who has a family relationship or the uncle of the victim's mother, by rubbing his genitals against the victim's vagina and rectum until sperm is released. As for Decision Number 1162/Pid.B/2021/PN.Bdg. The essence of the issues raised are, 1) Is the act of perpetrators of sexual abuse of children committed by family members appropriate or not based on Article 82 paragraph (1) in conjunction with Article 76E of Law Number 35 of 2014? 2) Is the criminal sanction of molestation of a child committed by a family member being terminated for 5 years, is it appropriate or not with the aim of punishment? This research uses normative research type and is analytical descriptive in nature, uses secondary data obtained through literature studies and is analyzed qualitatively by using deductive logical conclusions. The conclusions of this writing are, 1) The acts of perpetrators of molestation against children by family members are not appropriate based on Article 82 paragraph (1) in conjunction with Article 76E of Law Number 35 of 2014. The criminal sanction of molestation of children by family members is terminated for 5 years is not appropriate with the aim punishment. The research results of the perpetrators are related to the purpose of punishment, so the perpetrators should be subject to Article 82 paragraph (2) in conjunction with Article 76E of Law Number 17 of 2016.